Exploration of novel predictive markers in rat plasma of the early stages of chronic renal failure - Kobayashi, Toshihiro; Matsumura, Yuriko; Ozawa, Toshihiko; Yanai, Hiroyuki; Iwasawa, Atsuo; Kamachi, Toshiaki; Fujiwara, Kouichi; Tanaka, Noriaki; Kohno, Masahiro (Analytical and bioanalytical chemistry, 2014)
To identify blood markers for early stages of chronic kidney disease (CKD), blood samples were collected from rats with adenine-induced CKD over 28 days. Plasma samples were subjected to metabolomic profiling by liquid chromatography-mass spectrometry, followed by multivariate analyses. In addition to already-identified uremic toxins, we found that plasma concentrations of N6-succinyl adenosine, lysophosphatidylethanolamine 20:4, and glycocholic acid were altered, and that these changes during early CKD were more sensitive markers than creatinine concentration, a universal indicator of renal dysfunction. Moreover, the increase in plasma indoxyl sulfate concentration occurred earlier than increases in phenyl sulfate and p -cresol sulfate. These novel metabolites may serve as biomarkers in identifying early stage CKD.